Perencanaan dan Perancangan Wellness Center Di Desa Kelusa, Payangan, Gianyar, Bali - Nadya Mihiro Putri; Ni Wayan Nurwarsih; I Wayan Runa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Mental health is an important aspect in realizing overall health. However, in most developing countries, mental health problems have not been prioritized. The Coronavirus-19 (COVID-19) pandemic has made mental health an important issue in the world. The World Health Organization (WHO) identifies mental health as an integral component of the response to COVID-19. The COVID-19 pandemic with its massive transmission and high mortality rate causes problems that lead to mental disorders. A community-based approach can expand the scope of mental health services during the COVID-19 pandemic. The public will be required to live in a new normal state to maintain mental health and safety. Wellness Center is a place for people to recover their mental wellness which is located in a quiet, quiet, safe and comfortable place. The activities that can be done at the Wellness Center include yoga, meditation, sports, self-indulgence, and self-healing.